(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The Umayyad state has raised on a basic support represented by Arab discrimination . In time the prospect of the Islamic call has expended . The Arab Islamic world parties have expended to include Arabs and non Arabs of different races . the supporters have become as second center in the literary status and the social treatment on both . The political parties have noticed that there is a type of a complaint of the supporter so they attracted them to it . This discrimination has extended to include the Arabs themselves so they sided with the tribe bloc and persecuted others . The conflict has been between Arabs and non Arabs and between Arabs themselves Yemen and Al-Qaysiyah,This was one of the reasons for the deterioration of the Umayyad state and its fall .